Lucro real x lucro presumido em empresas de produtos alimentícios: o caso da Distribuidora Farias Ltda - (:unkn) unknown (Universidade Federal do Amazonas, 2011)
Inaccordance with the themespresented, the survey was developedas thegoalwas to showabetterstrategicoption to taxfor the companyDistribuidoraLtdaFarias. Consideringthe possibilitiesof optionsestimatedtaxbetweentaxable incomeand theAssumed Income. Tomeet the goalwas adoptedbythe case studymethodwhich is based ondescriptiveexploratory researchin orderto interpret the resultsto understand thehistorical processes andconceptsabout the topicbased onthe perceptionof a phenomenonin a certaincontext.Theresearch was conducted throughthe collection of informationondirect and indirectdocumentationprovided by the companyfor the period from2009to 2010, which are considered of paramountimportance tothis work. Data collectionwas performed atFariascompany DistribuidoraLtda., Located in the city ofManaus/ AM, concentrating research intax paymentsthrough theAssumed Incomewhiledoingasimulation for thetaxable incomein order toobserve thecomparison betweenboth.Through this comparisonwe determine theadvantages anddisadvantagesin relation toincometaxationbyPresumedor Real. We emphasizethat the studylooked mainlytaxthe branchof business activityand percentageof costs,expenses andprofit marginspredictable.After reviewingthe documents of thecompanystudied waspossible to prepareademonstrationcomparing thetaxes paidin thequarter to quarteras muchasRealModeNetIncomeAssumedexercisesof2009and 2010, which evidencedthatthe companystudiedthe maintenance of thepresumed profithadeconomic advantages.
Keywords: Tributação; Lucro real; Lucro presumido; Contribuição; Taxation; Real Earnings; IncomeTax; Presumed; CIÊNCIAS SOCIAIS APLICADAS: ADMINISTRAÇÃO